Study on the Transmission Characteristic of Plane Sinusoidal Steel Pin Drive Mechanism - Li Meiqiu; Luo Jingbo; Lu Bo (Jixie chuandong)
The cylindrical sine oscillating tooth transmission mechanism has the characteristics of small radial size,compact structure and high transmission efficiency. However,due to the complexity of the space sine curve groove,it is difficult to process and install,and the closed inner cavity is not conducive to heat dissipation. The research adopts the fixing output,holder,no eccentric plane sinusoidal steel pin drive mechanism,with good heat dissipation,the lack of space sine reducer is compensated. By analyzing the working principle and transmission characteristics of the plane sine steel pin drive structure,the method of judging the output rotation direction is obtained,and the formula of its transmission ratio is deduced. The kinematic characteristics and accuracy of the device are verified by kinematics simulation,the basis for the design and application of the mechanism is provided.